Challenges and dilemmas of social cohesion between the Rohingya and host communities in Bangladesh - Siddiqi, Bulbul (Frontiers in Human Dynamics, 2022)
Rising social tension is a potential cause of conflict among refugees and the host community. The UN and many international organisations have taken initiatives to promote social cohesion in ensuring the peaceful coexistence of the refugee and host community throughout the world. Much of such attention was given to the Syrian and other refugees in various western countries. However, social cohesion was not explored much in the Rohingya and host community perspective in Bangladesh. Although the Rohingya crisis in Bangladesh is not new, social cohesion was not much in the discussion in the past. But the influx of nearly one million Rohingya in Bangladesh in 2017 worsened the situation. After four years of the influx, when the repatriation has not been the reality for the Rohingya in Bangladesh, social cohesion between the Rohingya and the host community has become more complex than ever. The host community were sympathised with the large numbers of displaced Rohingya and extended their support to take refuge in Cox's Bazar. However, the sympathised attitude of the host community has significantly declined during the past four years. Under this context, this paper, based on qualitative research, aims to understand the challenges and dilemmas of social cohesion from the host and Rohingya perspectives. Based on 50 key informant interviews, observations, and several informal group discussions, the paper argues that a negative perception among the neighbouring host communities about the Rohingya has increased, contributing to social tension between them. Although the Rohingya generally seem to be thankful to the host community and wish to go back to their home country with dignity, the sense of social tension with the locals has been on the rise in recent times. Both communities perceive that anti-social activities are on the rise due to the influx of the Rohingya. Thus, the paper shows that a pragmatic and sustainable approach has to be taken to ensure a cohesive and peaceful coexistence of the host and Rohingya until we see any practical signs of dignified repatriation of the Rohingya.